13 gifts / 3. - Mass, Wendy, 1967- (Willow Falls, 2011)
Tara, a self-proclaimed shrinking violet, tries to break out of her shell by stealing the school mascot, a goat, but she gets caught and is shipped off for the summer to stay with relatives in the quirky town of Willow Falls, which she decides is as good a place as any to reinvent herself.